2003
DOI: 10.1016/s1097-2765(03)00175-8
|View full text |Cite
|
Sign up to set email alerts
|

Opposed Regulation of Corepressor CtBP by SUMOylation and PDZ Binding

Abstract: The transcription corepressor CtBP is often recruited to the target promoter via interaction with a conserved PxDLS motif in the interacting repressor. In this study, we demonstrate that CtBP1 was SUMOylated and that its SUMOylation profoundly affected its subcellular localization. SUMOylation occurred at a single Lys residue, Lys428, of CtBP1. CtBP2, a close homolog of CtBP1, lacked the SUMOylation site and was not modified by SUMO-1. Mutation of Lys428 into Arg (K428R) shifted CtBP1 from the nucleus to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
146
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 32 publications
10
146
2
2
Order By: Relevance
“…Sumoylation of factors regulating other domains of Net could have had effects in our assays. The repressor domain CID interacts with CtBP1, which is sumoylated with the help of PIAS1 and PIAS xb (Lin et al, 2003), as well as a different type of E3 enzyme, the polycomb protein Pc2 (Kagey et al, 2003). In analogy with Elk-1 and Sap-1 (Janknecht and Nordheim, 1996a, b), the activated C-domain of Net may interact with p300, which is a substrate for sumoylation (Girdwood et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sumoylation of factors regulating other domains of Net could have had effects in our assays. The repressor domain CID interacts with CtBP1, which is sumoylated with the help of PIAS1 and PIAS xb (Lin et al, 2003), as well as a different type of E3 enzyme, the polycomb protein Pc2 (Kagey et al, 2003). In analogy with Elk-1 and Sap-1 (Janknecht and Nordheim, 1996a, b), the activated C-domain of Net may interact with p300, which is a substrate for sumoylation (Girdwood et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo assays revealed that sumoylation of KLF3 is enhanced by E3 ligases of the protein inhibitors of activated STATs (PIAS) family, including PIAS1, PIASc, ARIP3, and MIZ1. The interaction of KLF3 with UBC9 is of interest, given that CtBP also binds UBC9, and sumoylation of CtBP is important for its nuclear localization and, therefore, function as a transcriptional corepressor (30). However, it appears that the recruitment of UBC9 by CtBP is not required for sumoylation of KlF3, given that mutation of the CtBP-binding site did not affect the ability of KLF3 to be sumoylated.…”
Section: Post-translational Modifications Of Klf3mentioning
confidence: 99%
“…8), suggesting that the sumoylation status of Hipk may be crucial for its role in regulating JNK activation. It has been reported that sumoylation can alter protein localization and/or change protein conformation (Geiss-Friedlander and Melchior, 2007;Girdwood et al, 2004;Lin et al, 2003;Sanchez et al, 2010;Zhong et al, 2000). To investigate the role of sumoylation on Hipk subcellular localization, we separated the nuclear and cytosolic fractions of the extracts from Hipk-expressing adult fly heads with or without smt3-RNAi expression.…”
Section: Depletion Of Smt3 Leads To Translocation Of Hipk From the Numentioning
confidence: 99%
“…This post-translational modification, termed sumoylation, plays important physiological roles by regulating various cellular activities. Extensive studies have revealed that sumoylation plays important roles in a variety of cellular processes such as transcriptional regulation, nuclear-cytoplasmic transportation, nuclear organization and DNA repair (Chen and Qi, 2010;Dou et al, 2010;Heun, 2007;Lin et al, 2003;Rui et al, 2002). Similar to the ubiquitylation process, sumoylation is achieved through sequential enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%